European Respiratory Society International Congress 2018: four shades of epidemiology and tobacco control. Issue 1 (4th March 2019) - de Vries, Maaike; Axson, Eleanor L.; Ratanachina, Jate; Dumas, Orianne; De Matteis, Sara; Bédard, Annabelle; Roda, Célina; Moitra, Subhabrata; Dagli, Elif; Diamanti, Athina; Dilektasli, Asli Gorek; Ravara, Sofia; et al.
In this article, early career members and experienced members of the Epidemiology and Environment Assembly of the European Respiratory Society highlight and summarise a selection of six sessions from the Society's annual congress, which in 2018 was held in Paris, France. The topics covered in these sessions span from cutting-edge molecular epidemiology of lung function to clinical, occupational and environmental epidemiology of respiratory disease, and from emergent tobacco products to tobacco control. Highlights of #ERSCongress 2018 from @ERStalk Assembly 6 http://ow.ly/O03v30nEHhJ